AR-based Taxi Recommendation by Leveraging Crowd Sharing Comments - Chen, Hsi-Min; Chen, Yan Ting; Ho, Yu; Yan, Yi Xiang (2018 15th International Symposium on Pervasive Systems, Algorithms and Networks (I-SPAN), 2018)
In recent years, with the growth of sharing economy where everyone can serve as a provider to offer various services, business models are different from the past. The most representative of them is Uber, which provides passengers with transparent information, such as driver rating and driving path, to let them trust drivers. However, Uber is not legal in Taiwan, so most of people needing transportation servers choose to take taxis. When people take taxis, they usually worry about safety, driver's driving habits, irregular billing, and detour. Therefore, we develop a taxi recommendation platform for passengers to select taxis based on the comments shared by previous passengers. Before users get into taxis, they can get taxi's ratings by means of AR with plate recognition technology and obtain the estimations of taxi fares. Besides, our platform is able to warn users of the divergence of driving routes during they are taking taxis. Finally, users can leave comments and ratings with respect to drivers via our platform after they get out taxis.